Effects of Dietary Yucca Schidigera Extract and Oral Candida utilis on Growth Performance and Intestinal Health of Weaned Piglets - Yang, Zhenguo; Wang, Yao; He, Tianle; Ziema Bumbie, Gifty; Wu, Liuting; Sun, Zhihong; Sun, Weizhong; Tang, Zhiru (Frontiers in Nutrition, 2021)
Economic benefit is an important goal pursued by animal husbandry industry. The emergence of antibiotics has promoted the development of animal husbandry, but many problems caused by the abuse of antibiotics have caused concerns about the use of antibiotics from all walks of life. Therefore, it is imperative to find alternatives to antibiotics. Studies have shown that plant extracts and probiotics have certain potential in improving animal growth performance, antioxidant capacity and immune function. The purpose of this study was to explore the effects of Yucca Shidigera Extract (YSE) and Candida Utilis (CU) on weaned piglets. We compared and evaluated the effects of YSE and CU on weaned piglets from the aspects of growth performance, immunity, antioxidant function, ileal morphology and microflora changes. In a 28-day study, a total of 40 healthy weaned piglets (Rongchang pig×Landrace×Large white) were randomly allocated into four groups: (1) control group (CON); (2) CU; (3) YSE; (4) CU+YSE. Our results showed that YSE and CU improved the growth performance by significantly increasing final weight, average daily gain (ADG) (P < 0.05), and there is decreasing trend of feed/gain ratio (P=0.087). The effect of adding YSE or CU alone on growth performance had little difference, and the effect of oral CU was slightly better than that of adding YSE. At the same time, the combination of YSE and CU had a good effect on reducing the diarrhea rate. In addition, both YSE and CU increased the diversity of cecal microflora, and CU increased the diversity more significantly, but did not change the dominant microflora of cecum. We also found that the addition of YSE and CU could maintain the structural integrity of intestinal tissue and regulate intestinal pH, to maintain the level of intestinal-associated immune proteins. At the same time, YSE and CU have certain benefits in regulating intestinal flora. YSE and CU could improve the growth performance, reduce the diarrhea rate, improve intestinal health, and increase the diversity and abundance of cecal microflora in weaned piglets. Therefore, YSE and CU are expected to be used as probiotics in the production of weaned piglets.